Wetsuit use during open water swimming. does it "suit" everybody? A narrative review - Quagliarotti, C.; Cortesi, M.; Gatta, G.; Bonifazi, M.; Zamparo, P.; Baldassarre, R.; Vleck, V.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Although wearing a wetsuit while swimming, when permitted, is primarily for safety reasons (ie, to protect against hypothermia), changes in buoyancy, biomechanics, and exercise performance have been reported. This narrative review covers the benefits of different wetsuit models on performance in swimming and triathlon.